Evaluación de la experiencia del usuario en conceptos de diseño y arquitectura contemporáneos, mediante el uso de herramientas de tecnología digital pertinentes - Buitrón Cevallos, Orlando André (2017)
The following work is a theoretical contribution, starting with the analysis of architecture referents who explain design styles and how projectile science have been evolving in the long run, in addition it presents the summary of some topic of Patrick manifest of Shumacher “The Autophoiesis of Architecture”, the same that states a design paradigm that, according to him, didn’t exist in design’s modernist style, which is based in Parametricism, in which it’s possible to amplify its use with the help of digital construction technology of the fourth industrial revolution. In this thesis, there’s an analysis further than architecture, where its extended into various design activities oriented to product and industrial design. This theory was applied over a parametric structure of exhibition which was made of wood and was shown in CROMIA 2015, which is subject of experiments monitored by “Universidad de Las Américas” in Granados campus for 3 days. This project has as its first goal to “Elaborate a methodology of concept application of contemporary design and architecture using digital technology tools” as Quito, Ecuador “Universidad de Las Americas” investigation plan which will also feed the necessary information for the project of two thesis students that will continue this work, and which will cover other thesis with similar products